CARCINOLOGICAL STUDIES XX THE TAXONOMIC SIGNIFICANCE OF THE THIRD MAXILLIPED IN THE GENUS PENAEUS - RIOJA, ENRIQUE (Hospital General, CD MEXICO, DF, MEX, 1964)
Alectryonia nicaisei var bolivari and Inoceramus goldfussianus apparently represent tow levels of the Middle Senonian, perhaps more exactly the Campanian, and are the first known of this age from Peru
ANS INST BIOL
Keywords: CARCINOLOGICAL STUDIES XX, TAXONOMIC SIGNIFICANCE, THIRD MAXILLIPED, GENUS PENAEUS; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; ZOOLOGIA GENERAL